Microbial Diseases of Marine Organisms - Zrnčić, Snježana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book, entitled "Microbial Diseases of Marine Organisms", was conceived to raise awareness of threats to the sustainability of marine environments that we are increasingly facing today and are caused by various human activities. Each marine organism plays a unique role in the marine ecosystem, regardless of whether it is prey or predator or its status in the food chain. Microorganisms such as protists, bacteria, fungi, and viruses mostly share mutually beneficial symbiotic relationships, with their hosts. However, environmental changes, including climate change, which are mostly induced by anthropogenic impacts, can affect these relationships and consequently influence the health, welfare, physiology, and ecology of marine organisms and environments. Many microorganisms have exhibited changes in nature and have been reported as causes of diseases or mortality of marine organisms. These disease outbreaks may lead to declines in the host populations, resulting in changes in diversity and imbalances in marine environments.